2014
DOI: 10.1603/ec13204
|View full text |Cite
|
Sign up to set email alerts
|

Southern Rice Black-Streaked Dwarf Virus Infection Improves Host Suitability for Its Insect Vector, <I>Sogatella furcifera</I> (Hemiptera: Delphacidae)

Abstract: The impact of southern rice black-streaked dwarf virus (SRBSDV) on the life cycle of the vector Sogatella furcifera (Horváth) (Hemiptera: Delphacidae) was investigated. The adult longevity was significantly shorter when the insect was reared on the SRBSDV-infected rice plants than those reared on the noninfected rice treatment. The fecundity of S. furcifera reared on the SRBSDV-infected rice plants was slightly higher than that of those reared on the noninfected rice plants both in macropterous and brachyptero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…In this study, nonviruliferous white-backed planthopper females exposed to infected rice seedlings lived longer than the other three treatment groups. These results which are similar to those reported for other virus vectors such as A. gossypii on zucchini plants infected by ZYMV (Blua et al 1994) and B. tabaci on tobacco plants infected by TYLCCNV (Jiu et al 2007), and contradict the reports by Tu et al (2013) and Zhang et al (2014), who found an adverse effect of SRBSDV-infected rice plants on adult white-backed planthopper longevity. The contrasting results may result from difference in experiment designs.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In this study, nonviruliferous white-backed planthopper females exposed to infected rice seedlings lived longer than the other three treatment groups. These results which are similar to those reported for other virus vectors such as A. gossypii on zucchini plants infected by ZYMV (Blua et al 1994) and B. tabaci on tobacco plants infected by TYLCCNV (Jiu et al 2007), and contradict the reports by Tu et al (2013) and Zhang et al (2014), who found an adverse effect of SRBSDV-infected rice plants on adult white-backed planthopper longevity. The contrasting results may result from difference in experiment designs.…”
Section: Discussionsupporting
confidence: 85%
“…results, although they found a temperature-dependent effect on the wing form ratio. The ratio of macropterous adults was reported to be increased by SRBSDV infection of rice, where they reported a ratio of macropterous males as high as 47.9 Ð 69.4% (Zhang et al 2014), which was extraordinary higher than previously reported results (Liu et al 2010). In this study, nonviruliferous white-backed planthopper females exposed to infected rice seedlings lived longer than the other three treatment groups.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…However, the infection of rice reoviruses in rice plants may alter the attractiveness of rice plants to the insect vector. For example, SRBSDV-infected plants are more attractive to nonviruliferous S. furcifera individuals but less so to the viruliferous ones, whereas healthy plants are more attractive to the viruliferous but less so to the nonviruliferous individuals (131). Furthermore, RRSV-carrying N. lugens individuals prefer SRBSDV-infected rice plants (62,104).…”
Section: Ecological Impacts Of Virus-insect-plant Interactionsmentioning
confidence: 99%